Social entrepreneur and gender: what’s personality got to do with it? - Bernardino, Susana (2018)
Purpose – Research on economic entrepreneurship identifies a gender gap that is favorable to men. In the social entrepreneurship arena, the existing evidence is slightly fuzzy, as this gender gap is less preeminent. This paper aims to identify how gender differences in social entrepreneurial ventures creation are explained by different personality traits, by analyzing the extent to which female and male social entrepreneurs exhibit the same personality traits and whether potential differences are able to explain the differences in predisposition for the creation of new social entrepreneurial ventures. Design/methodology/approach – A review of the literature on gender differences and personality traits in social entrepreneurship details the main theoretical developments and builds the hypotheses. Based on the Big Five model, the investigation uses a hypothesis testing quantitative approach. Primary data were collected through a questionnaire that was e-mailed and applied to the social entrepreneurs engaged in the creation of social ventures in Portugal. Findings – The data gathered suggest that both female and male social entrepreneurs have personalities characterized by high levels of openness to experience, agreeableness, conscientiousness, extraversion and emotional stability. Based on the analysis of variance (ANOVA) between the two groups and logistic regression, the investigation reveals that women and men who launch a new social venture only differ in one personality dimension – agreeableness – wherein women scored more highly. No significant differences are found in the other personality traits. Research limitations/implications – The research assumes that most aspects of human personality structure are represented in the Big Five model. Practical implications – The knowledge about whether gender differences are explained by different personality traits is critical to public entities that might design appropriate public policies to stimulate social entrepreneurship. Also, social entrepreneurs’ capacity building programs should be delineated in accordance with a deeper understanding about gender and personality traits differences. Social implications – The knowledge of the factors that affects the creation of new social ventures has an important potential contribution on social value creation and the promotion of gender equality. Originality/value – This paper links two important topics – gender and entrepreneurs’ personality traits – scarcely explored in the social entrepreneurship literature. Thus, the paper adds new empirical evidence to support (or not) the belief that personality and gender matter in the decision to launch a new social venture.